Effect of Y on oxide film formation and ignition behavior of magnesium-rare earth alloy - Longbiao Feng; Hongxian Shen; Lunyong Zhang; Ziao Qiu; Fuyang Cao; Zhiliang Ning; Yongjiang Huang; Jianfei Sun (Journal of Magnesium and Alloys)
The incorporation of Y significantly improves the fire resistance of the Mg-3Nd-2Gd-0.2Zr-0.2Zn (EV32) alloy. The findings indicate a significant increase in the ignition point of the alloy upon Y addition, notably reaching 813.9 °C for the EV32–3Y (wt.%) alloy. Additionally, the calculated residual stresses of the Y2O3 and Gd2O3 films were 2.732 GPa and 2.569 GPa respectively, showcasing a distinct correlation between Y concentration and improved fire resistance. This enhancement can be attributed to the formation of denser oxide films, especially Y2O3 and Gd2O3, effectively reducing the susceptibility of the oxide film to thermal stress-induced tearing. The study elucidates the vital role of Y addition in enhancing fire resistance, thoroughly investigating the mechanisms that impact both the formation of oxide films and ignition within the alloy structure. These findings not only contribute to a deeper comprehension of magnesium alloy performance under high-temperature conditions but also offer valuable theoretical guidance for enhancing its fire resistance through alloy design and application.